Los derechos laborales en el trabajo agrícola de la parroquia San Pablo de Atenas año 2022. - Tapia Vásquez, Brillid Yadira (2024)
This research entitled: "Labor rights in agricultural work in the parish of San Pablo De Atenas year 2022" covers the rights of agricultural workers, as determined by the Constitution of the Republic of Ecuador and the regulations of domestic law constant in the Labor Code. Therefore, it is essential to investigate the problem of the violation of the rights of agricultural workers, given the precarious relationship between employer and worker, mainly by entering into an individual employment contract, but one of a verbal nature, so that the rights and obligations are not specified. In another way, the constant non-compliance with the agreed wages, without observing the maximums, nor the mandatory breaks and, possibly, what is even worse is that the agricultural worker does not receive any type of labor benefits, such as thirteenth, fourteenth or utilities, all of which constitutes a violation of the labor rights of the agricultural worker. Therefore, guaranteeing this right is an imperative and unavoidable necessity, since we also start from the fact that this benefit is not a mere precept, but a fundamental right, which must be produced in its maximum expression. This research is important because agricultural workers must receive adequate state protection to guarantee their constitutional and legal rights; they must also know the mechanisms through which they can make them effective when they are subject to violations by their agricultural employer. In this way, the agricultural worker, whether he is a day laborer or a pieceworker, can be safeguarded in his rights, without prejudice to the fact that the work is performed by task or by the fixing of a remuneration based on custom, as would be the case of the supporters who agree to work by delivering a part of their harvest to the agricultural employer or owner of the land. In this particular case, it must be said that the split contract is a modality widely used in agricultural work throughout Ecuador and especially in the parish of San Pablo de Atenas due to the high population that is dedicated to this activity, because it benefits the employer who 4 only delivers a plot and certain inputs to the agricultural worker, who uses his outside labor to produce the crops. Therefore, the agricultural employer evades all the labor rights to which he is obliged with the agricultural worker, mainly: the payment of a remuneration established in the sectoral minimums, payment of legal benefits, labor stability because the agricultural work is only produced seasonally. On the other hand, it should be noted that agricultural work is usually carried out by means of a verbal labor contract, in order to avoid constituting the labor relationship between the employer and the worker, thus avoiding the claim of labor rights, in good synthesis the modality of the split contract violates in every way the rights of the agricultural worker. Methodology: The research approach is qualitative and its scope is correlational in nature. The most general research methods were applied, such as: inductivedeductive method, analytical-synthetic method, historical-logical method and scientific method; and the research technique used was the survey through the application of a questionnaire. Finally, conclusions were drawn. Key words: labor rights, agricultural worker, employer, state protection.